Estudo taxonômico dos Cecidomyiidae (Diptera) associados a galhas de Myrtaceae na Restinga da Barra de Maricá, Rio de Janeiro - Maia, Valéria Cid (1994)
Fourteen different galls were observed on six species of host-plants, each one made by a distinct species of Cecidomyiidae. Besides these gallmakers, seven inquiline or predator species of Cecidomyiidae were also found. As result of this study three new genera and eleven new species of Cecidomyiidae were found and described on papers already published or waiting for publication. Some new occurences were recorded for the first time: 1) Trotteria Kieffer, 1901 in Brazil and in galls of Stephomyia Tavares, 1916 galls (Trotteria was considered as a specialist in Asphondylia Loew, 1850 galls), 2) Neomitranthes as host plant of Stephomyia, 3) Resseliella Steiner, 1906 in South America and 4) Lestodiplosis Kieffer, 1894 and Neolasioptera Felt, 1908 on Myrtaceae.